(untitled) - Reider, Rob (Business Expert Press, 2012)
Ebook from IG Library ; Striving for excellence in customer service to gain the competitive advantage is the keystone for the business to grow and prosper in the right direction so that it builds through repetitive sales to existing customers and referrals to potential customers. If customer service is looked at as a major business component and all customers are treated with excellence prior to the sale, during the sale, and after the sale, customer service will become a profit center that builds sales dollars to the top line and real profits to the bottom line. It is just as easy to provide really excellent customer service, as it is to deliver poor customer service that drives the customers to the competition.
Keywords: Marketing Strategy; Chiến lược tiếp thị; Quản lý tiếp thị